SIMULASI LINTASAN JALUR TERPENDEK ALGORITMA DIJKSTRA BERBASIS EXTENSIBLE MARKUP LANGUAGE (XML) - WIDODO, ARIS PUJI (MATEMATIKA, 2007)
Â An optimation is a classical problem to use determine decision making. Traditionally to solve an optimation problem, it is needed a precission and long time. The improvement of this problem, needs simulation software development, less time relatively, and the result more than manually calculated, cause error probability to much. This research concern to make a simulation software based on Dijkstra Algorithm, as tool to give informations on the optimation decision making. Â